Performance and emission characteristics of Mahua oil biodiesel in low heat rejection diesel engines with retarded injection timing - Ratchagaraja Dhairiyasamy; Deepika Gabiriel (Chemical Thermodynamics and Thermal Analysis)
The study investigates the performance, combustion, and emission characteristics of Mahua oil in a low heat rejection (LHR) diesel engine with retarded injection timing. Mahua oil, a non-edible biodiesel, was evaluated against conventional diesel in both coated and uncoated engine configurations. The engine coated with partially stabilized zirconia (PSZ) showed significant improvements. Brake thermal efficiency (BTE) increased by 9.15 %, and specific fuel consumption decreased by 6.23 % compared to the standard uncoated engine. Emission analysis revealed a reduction in carbon monoxide (CO) and unburnt hydrocarbons (UBHC) by 20.35 % and 12.28 %, respectively. However, nitrogen oxide (NOx) emissions increased by 5.36 % due to the higher combustion temperature induced by the PSZ coating. Exhaust gas temperature (EGT) also rose by 18.64 %, highlighting enhanced combustion. The study concludes that Mahua oil, when used in an LHR engine with retarded injection timing and PSZ coating, offers improved efficiency and reduced emissions, making it a viable alternative to diesel in specific applications. Future work should explore the effects of varying compression ratios and different biodiesel blends to optimize engine performance further.